DIGITAL DIDACTIC MODEL FOR DEVELOPING PROGRAMMING COMPETENCE IN ENGINEERS WITHIN A DIGITAL LEARNING ENVIRONMENT (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In the context of the digitalization of engineering education, there is an increasing need to develop didactic models that foster sustainable programming competence among students in technical fields. The aim of this study is to design and pilot a digital didactic model implemented on the ITTS platform, which ensures systematic development of algorithmic thinking, programming skills, and readiness for professional activity. The methodological framework of the model comprises four interrelated components: the target component (strategic objectives of engineering education), the organizational-methodological component (competence-based model, principles of systematization, integration, and practice orientation), the content component (ITTS digital platform, theoretical and practical elements, visual learning tools), and the diagnostic component (competence assessment through testing, project defense, and analysis of performance dynamics). The empirical validation of the model was conducted through a pedagogical experiment involving control and experimental groups. The collected data confirm a statistically significant improvement in academic performance, increased student engagement, and enhanced cognitive coherence. The main conclusion affirms the effectiveness of the proposed model, its reproducibility, and its potential for scaling across other engineering disciplines.